How Costly Is External Financing? Evidence from a Structural Estimation - HENNESSY, CHRISTOPHER A.; WHITED, TONI M. (Journal of Finance, 2007)
ABSTRACT We apply simulated method of moments to a dynamic model to infer the magnitude of financing costs. The model features endogenous investment, distributions, leverage, and default. The corporation faces taxation, costly bankruptcy, and linear‐quadratic equity flotation costs. For large (small) firms, estimated marginal equity flotation costs start at 5.0% (10.7%) and bankruptcy costs equal to 8.4% (15.1%) of capital. Estimated financing frictions are higher for low‐dividend firms and those identified as constrained by the Cleary and Whited‐Wu indexes. In simulated data, many common proxies for financing constraints actually decrease when we increase financing cost parameters.